Average angular momenta of the fragments in 238U photofіssіon with bremsstrahlung - І. M. Vyshnevskyі; V. O. Zheltonozhsky; A. M. Savrasov; V. А. Plujko; О. М. Gorbachenko; K. М. Solodovnyk (Ядерна фізика та енергетика)
Based on 238U photofission experiments with the bremsstrahlung photons, the isomeric yield ratios were measured for 95Nb and 133Xe nuclei at the end-point energy Ee = 12.5 MeV, and 135Xe nuclei at Ee = 12.0 MeV. Experimental values of isomeric yield ratios were obtained taking into account the contribution from beta-decay of isobaric nuclei in yields of investigated isotopes. Average angular momenta of investigated fission fragments were determined using the statistical model of decay.